ASPEK PIDANA DISKRIMINATIF TERHADAP PELAYANAN PASIEN KURANG MAMPU BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Afiyfah Nabila; Maria Maya Lestari; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Adult health service is an important issue to increase the standard of living and social welfare in our homeland (Indonesia). A form of health service implementing regulations is law number 36/2009 about health, in which in the law on health, there is should not be discrimination. Furthermore, the aims of this research are: first, to identify the adjustment about sentencing towards discriminatory perpetrators to health’s services. Second, to classify the law of accountability towards discriminatory health’s services against poor patients based on law number 36/2009 about health.Moreover, this law study is using normative legal research. An approach that is used for this study is normative juridical approach. Also, this study use qualitative data for finding the justification. Later on, to get the conclusion the researcher uses deductive thinking method where getting the conclusion by adopting statements or law of general nature to be specific statements.Lastly, sentencing towards discriminatory perpretators health services based on law can be addressed when fullfiled by several factors from article 32 (2) such as; rejection and asking for down money towards health service’s patients which stated article 190, law number 36/2009 about health. The parties that can be asked for the responsibility against discrimination towards indigent patient divided in general and particular. Thereafter, in general this case occur on article 304 and article 531 KUHP. Whereas, in particular this matter stated on article 190 law number 36/2009 about health.Key words: Discriminative – Health Service – Law on Health